2021
DOI: 10.3390/microorganisms9071519
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and Type 1 Diabetes: From Enteroviruses to the Virome

Abstract: For over a century, viruses have left a long trail of evidence implicating them as frequent suspects in the development of type 1 diabetes. Through vigorous interrogation of viral infections in individuals with islet autoimmunity and type 1 diabetes using serological and molecular virus detection methods, as well as mechanistic studies of virus-infected human pancreatic β-cells, the prime suspects have been narrowed down to predominantly human enteroviruses. Here, we provide a comprehensive overview of evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 257 publications
(330 reference statements)
1
29
0
Order By: Relevance
“…Despite the evolving knowledge on the subject, the pathological mechanisms that trigger the initiation and progression of CVB-induced autoimmunity against islet antigens in T1DM are not yet fully elucidated. Experimental data suggest various mechanisms to explain the initiation of autoimmunity by CVB; for example, molecular mimicry between the conserved enteroviral protein 2C and glutamic acid decarboxylase, or bystander activation of pre-existing autoreactive T cells through the initiation of inflammation 11 , 22 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evolving knowledge on the subject, the pathological mechanisms that trigger the initiation and progression of CVB-induced autoimmunity against islet antigens in T1DM are not yet fully elucidated. Experimental data suggest various mechanisms to explain the initiation of autoimmunity by CVB; for example, molecular mimicry between the conserved enteroviral protein 2C and glutamic acid decarboxylase, or bystander activation of pre-existing autoreactive T cells through the initiation of inflammation 11 , 22 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Like the rest of the world, Montenegro has been affected by the ongoing worldwide pandemic (COVID-19 pandemic) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus since its first case was confirmed on 17 March 2020. For more than 50 years, viruses are considered potential triggers for autoimmune diseases such as T1D (21,22). Furthermore, some authors reported an increased incidence of new-onset T1D during the first year of the COVID-19 pandemic (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…A possible infectious origin (in this particular case, the mumps virus) for T1DM was already proposed near a century ago (Gundersen 1927). To date, many studies have dealt with the possible involvement of different enteroviruses (more speci cally, coxsackievirus) in T1DM (for two recent comprehensive reviews, see Isaacs et al 2021 andLloyd et al 2022). Another factor supporting an infectious basis for T1DM is seasonality (Gamble et al 1969).…”
Section: Introductionmentioning
confidence: 99%